2014
DOI: 10.1007/s10552-014-0465-4
|View full text |Cite
|
Sign up to set email alerts
|

Parental occupational exposure and risk of childhood central nervous system tumors: a pooled analysis of case–control studies from Germany, France, and the UK

Abstract: Our large pooled study showed weak evidence of a modest association between paternal occupational exposure to PAH and CNS tumor risk. Our findings need further exploration in the future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…A similar conclusion can be reached for parental occupational exposure or for the exposure to different possible environmental factors [34][35][36][37].…”
Section: Risk Factorssupporting
confidence: 68%
“…A similar conclusion can be reached for parental occupational exposure or for the exposure to different possible environmental factors [34][35][36][37].…”
Section: Risk Factorssupporting
confidence: 68%
“…Estimations were performed using the general population DOM-JEM. [18][19][20] The DOM-JEM is based on the five-digit ISCO 1968 coding, 17 providing an exposure estimate (none, low, high) to each individual job code.…”
Section: Classification Of Occupational Exposuresmentioning
confidence: 99%
“… 15 These results were not replicated, however, in a pooled analysis of several European case–control studies with self-reported information on parental occupation, which found no association between maternal exposure to diesel EEF and CNS tumors. 16 …”
Section: Discussionmentioning
confidence: 99%
“…A recent Danish register–based study indicated that maternal occupational exposure to diesel EEFs led to higher risks of astrocytoma but not leukemia in the child. 15 However, previous studies based on self-reports of occupation or EEF exposure found no elevated risk for CNS tumors 16 but did find increased risks of ALL from parental, 17 paternal, 11 , 18 or maternal exposure. 11 , 19 Children whose fathers were exposed to gasoline EEF also appeared to be at risk of non-Hodgkin lymphoma in one study.…”
Section: Introductionmentioning
confidence: 86%